Trolox Antioxidant as a Factor in Stabilization of Human Cord Blood Nucleated Cells During Cryopreservation - Zubov , Pavlo; Zubova, Oksana; Babijchuk, Lyubov (Problems of Cryobiology and Cryomedicine, 2023)
The paper presents experimental data on the determination of preservation rate of human cord blood nucleated cells and their apoptosis/necrosis stages to determine the number of viable functionally active cells after cryopreservation in solutions with different concentrations of DMSO and the water-soluble analogue of vitamin E, the antioxidant trolox. Counting the number of human cord blood nucleated cells after freezing in media with the addition of trolox revealed their maximum preservation in the samples with 7.5% DMSO and 50, 70 or 200 μM of the antioxidant. Using the flow cytometry with the addition of the Annexin V FITC reagent, which specifically binds to phospholipids, and the DNA dye 7-amino-actinomycin D (7-AAD), it was established that trolox in concentrations of 50–70 μM provided an increase in the number of viable cells with intact membrane (AnnexinV─/7AAD─) by 12–16% compared to the control, which involved the use of only DMSO in the cryoprotective solution. The obtained results indicate the effectiveness of using the antioxidant trolox and the prospects of developing trolox-containing cryoprotective mixtures for freezing and long-term storage of nucleated cord blood cells, including hematopoietic progenitor cells. Probl Cryobiol Cryomed 2023; 33(2):122-132